A connected cytoskeleton network generates axonal tension in embryonic Drosophila. Issue 18 (22nd August 2019) - Fan, Anthony; Joy, Md Saddam Hossain; Saif, Taher
Abstract : A microfluidic system that can perform load-displacement test and apply partial treatment simultaneously allows us to reveal the in-series architecture of load-generating cytoskeleton in drosophila axons. Abstract : Axons of neurons are contractile, i.e., they actively maintain a rest tension. However, the spatial origin of this contractility along the axon and the role of the cytoskeleton in generating tension and sustaining rigidity are unknown. Here, using a microfluidic platform, we exposed a small segment of the axons of embryonic Drosophila motor neurons to specific cytoskeletal disruption drugs. We observed that a local actomyosin disruption led to a total loss in axonal tension, with the stiffness of the axon remaining unchanged. A local disruption of microtubules led to a local reduction in bending stiffness, while tension remained unchanged. These observations demonstrated that contractile forces are generated and transferred along the entire length of the axon in a serial fashion. Thus, a local force disruption results in a collapse of tension of the entire axon. This mechanism potentially provides a pathway for rapid tension regulation to facilitate physiological processes that are influenced by axonal tension.